2023
DOI: 10.3390/math11020364
|View full text |Cite
|
Sign up to set email alerts
|

DeepLabv3+-Based Segmentation and Best Features Selection Using Slime Mould Algorithm for Multi-Class Skin Lesion Classification

Abstract: The development of abnormal cell growth is caused by different pathological alterations and some genetic disorders. This alteration in skin cells is very dangerous and life-threatening, and its timely identification is very essential for better treatment and safe cure. Therefore, in the present article, an approach is proposed for skin lesions’ segmentation and classification. So, in the proposed segmentation framework, pre-trained Mobilenetv2 is utilised in the act of the back pillar of the DeepLabv3+ model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Two models closest to our precision performance were in accordance with [39] and [38], with 99.10% and 99.17%, respectively. Likewise, there were two closest models for the f1-score performance, such as in [40], and [41], with 98.60% and 97.24%, respectively. This comparison is detailed in Table 5.…”
Section: Performance Comparison Against Sotamentioning
confidence: 93%
“…Two models closest to our precision performance were in accordance with [39] and [38], with 99.10% and 99.17%, respectively. Likewise, there were two closest models for the f1-score performance, such as in [40], and [41], with 98.60% and 97.24%, respectively. This comparison is detailed in Table 5.…”
Section: Performance Comparison Against Sotamentioning
confidence: 93%
“…Budhiman et al [39] 87 (for normal and melanoma class) Bibi et al [32] 85.4 Mahbod et al [40] 86.2 Ali et al [41] 87.9 Carcagnì et al [42] 88 Sevli [43] 91.51 Mehwish et al [44] 92.01 Bansal et al [45] 94.9 (for normal and melanoma class)…”
Section: Study Accuracy (%)mentioning
confidence: 99%
“…In contrast, in [32], the deep features were extracted using the DensNet-201 and DarkNet-53, and a marine predator optimizer was applied to extract the useful features, an approach that yielded an accuracy of 85.4% for seven class ISIC2018 datasets. Furthermore, Mehwish et al [44] used a wrapper-based approach to remove the redundant deep features and reported a high accuracy of 92.01%. However, the feature selection approach with CNN can enhance the complexity and compatibility issues with dependencies on the external algorithms.…”
Section: Study Accuracy (%)mentioning
confidence: 99%
“…In [25][26][27][28][29][30][31][32][33][34][35], it was observed that the presence of irrelevant or redundant features may lead to the incorrect prediction of images and may bring down the classification results. Many techniques [25][26][27][28][29][30][31][32][33][34][35] employ feature selection (FS) algorithms for selecting the most appropriate features in order to maximize the classification performance.…”
Section: Related Workmentioning
confidence: 99%